2002
DOI: 10.1016/s0893-133x(01)00307-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Prolyl Endopeptidase Inhibitor S 17092 on Cognitive Deficits in Chronic Low Dose MPTP-Treated Monkeys

Abstract: A number of neuropeptides are affected in Parkinson's disease and the enzyme proline endopeptidase contributes to the degradation of many of these neuropeptides, some of which are linked to a variety of cognitive functions. In the present study, the effects of the highly potent proline endopeptidase inhibitor S 17092 on cognitive deficits in monkeys induced by chronic low dose 2,3, It is generally recognized that non-demented Parkinson's disease (PD) patients exhibit a number of neuropsychological deficits, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 18 publications
(29 reference statements)
2
57
0
1
Order By: Relevance
“…Various authors have reported an unusually higher PEP levels in the patients suffering from AD and suggested that PEP might be one of the several factors involved in cognitive decline associated with aging (Lee & Paik, 2003;Tezuka et al, 1999). Therefore, PEP inhibition might have a therapeutic value in the treatment of AD and PEP inhibitors could be a novel anti-amnesic drug Schneider et al, 2002;Toide et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported an unusually higher PEP levels in the patients suffering from AD and suggested that PEP might be one of the several factors involved in cognitive decline associated with aging (Lee & Paik, 2003;Tezuka et al, 1999). Therefore, PEP inhibition might have a therapeutic value in the treatment of AD and PEP inhibitors could be a novel anti-amnesic drug Schneider et al, 2002;Toide et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of these substrates led to new hypotheses about Prep function, which were tested in vivo using pharmacological Prep inhibitors. Interestingly, several of these experiments suggested that Prep inhibition would lead to improved cognitive function in mammals, which was later verified (15)(16)(17)(18). However, the underlying mechanism for this improvement is still under investigation because some of the Prep substrates predicted to be responsible for this effect were unaffected, or only modestly affected, upon Prep inhibition (19)(20)(21).…”
Section: Introductionmentioning
confidence: 86%
“…The unique biochemical activity of Prep, namely the ability to cleave peptides at proline amino acids, has prompted a great deal of research into the biochemical, cellular, and physiological functions of this protein (9). In vitro assays have identified Prep substrates that range from the tripeptide, thyrotropin-releasing hormone, to a 31 amino acid peptide, beta endorphin (9,34), which led to new hypotheses about the physiological role of Prep, including a role in cognitive function (15)(16)(17)(18).…”
Section: Peptidomics Of Prep In the Central Nervous Systemmentioning
confidence: 99%
“…AChE nausea, vomiting, bradycardia, anorexia sweating (Mehta et al, 2012 (Mannisto et al, 2007;Schneider et al, 2002;. PEP target .…”
mentioning
confidence: 99%